2019
DOI: 10.1186/s12934-019-1063-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequencing, genome-scale metabolic network reconstruction, and in silico flux analysis of the grape endophytic fungus Alternaria sp. MG1

Abstract: BackgroundAlternaria sp. MG1, an endophytic fungus isolated from grape, is a native producer of resveratrol, which has important application potential. However, the metabolic characteristics and physiological behavior of MG1 still remains mostly unraveled. In addition, the resveratrol production of the strain is low. Thus, the whole-genome sequencing is highly required for elucidating the resveratrol biosynthesis pathway. Furthermore, the metabolic network model of MG1 was constructed to provide a computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 87 publications
0
33
0
Order By: Relevance
“…In contrast, sequences with similarity to 4CL do occur in rhodophyte and chlorophyte genomes (Labeeuw et al, 2015;de Vries et al, 2017), suggesting the existence of this enzyme in a shared ancestor of land plants and algae before the ancestral divergence of the red algae (Labeeuw et al, 2015). A further aspect yet to be addressed is the presence in fungi of genes with significant sequence similarity to those of the phenylpropanoid pathway (Bilska et al, 2018;Lu et al, 2019). As the separation of fungi and plants is thought to have occurred during the early stages of eukaryote divergence (Burki, 2014;Burki et al, 2020), it is possible that these may represent cases of convergent evolution.…”
Section: The Phenylpropanoid Biosynthetic Pathway In Bryophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, sequences with similarity to 4CL do occur in rhodophyte and chlorophyte genomes (Labeeuw et al, 2015;de Vries et al, 2017), suggesting the existence of this enzyme in a shared ancestor of land plants and algae before the ancestral divergence of the red algae (Labeeuw et al, 2015). A further aspect yet to be addressed is the presence in fungi of genes with significant sequence similarity to those of the phenylpropanoid pathway (Bilska et al, 2018;Lu et al, 2019). As the separation of fungi and plants is thought to have occurred during the early stages of eukaryote divergence (Burki, 2014;Burki et al, 2020), it is possible that these may represent cases of convergent evolution.…”
Section: The Phenylpropanoid Biosynthetic Pathway In Bryophytesmentioning
confidence: 99%
“…Notably, in fungal species there have been recent reports of both the production of flavonoids and the presence of genes with significant sequence similarity to those of the phenylpropanoid pathway of land plants. Findings include the detection of a range of phenylpropanoids, including flavonoids, in Fusarium (Bilska et al, 2018) and detection of flavonoids and candidate genes for stilbene production in Alternaria (Lu et al, 2019). The significance of phenylpropanoid biosynthesis being present in fungi for the current proposals on the evolutionary origins of flavonoid biosynthesis has yet to be addressed.…”
mentioning
confidence: 99%
“…Based on these characteristics, a number of studies have shown that surfactin-based extraction has good prospects in MEOR [ 11 ]. The industrial application of surfactin is not limited by yield, since the surfactin production of engineered strains reached 10–20 g/L [ 12 ]. At present, the point of concern is the heterogeneity of surfactin structure, which closely affects the functional activity of surfactin preparations.…”
Section: Introductionmentioning
confidence: 99%
“…At present, strategies proposed to modify the structure of surfactin are all based on the metabolism of branched-chain amino acids, because some precursors for the synthesis of branched chain fatty acids presented in surfactin are derived from the branched chain amino acids valine, leucine and isoleucine [ 12 ]. For example, the proportion of surfactin with even β-hydroxy fatty acid components C 14 and C 16 increased with the addition of Arg, Gln or Val, whereas the addition of Cys, His, Ile, Leu, Met, and Ser enhanced the proportion of odd β-hydroxy fatty acids in B. subtilis TD7 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, high-throughput biotechnology has been used to study the mechanisms for microbial co-culture to produce polyketides, such as genome, transcriptome, metabolome and proteome. Besides, constructing genome-scale metabolic model has also been developed to predict the metabolic flow of co-culture system, which is helpful to clarify the interaction between micro-organisms and provides theoretical basis for the development of artificial intervention to the co-culture system (Lu et al 2019). In addition, cell fusion and gene engineering biotechnology can also be used to construct engineering cell, change the metabolic flow of micro-organisms or construct new metabolic pathways.…”
Section: Prospects Challenges and Solutionsmentioning
confidence: 99%